Emergence of Maruca vitrata as a major pest of food legumes and evolution of management practices in Asia and Africa - Srinivasan, R.; Tamò, Manuele; Malini, P. (Annual Reviews, 2021)
Legume pod borer, Maruca vitrata, has emerged as a major pest on food legumes in Asia and Africa. It is an oligophagous pest, feeding on over 70 species in Fabaceae. We examine the species complex in Asia, Africa, Oceania, and the Americas, with an emphasis on molecular taxonomy. Studies on pheromone production and perception suggest the existence of pheromone polymorphism, especially in Asia and Africa. No Maruca-resistant varieties are available in the major food legumes including cowpea, pigeonpea, mungbean, and yard-long bean. Legume growers use chemical pesticides indiscriminately, leading to the development of pesticide resistance. However recent developments in habitat management, classical biocontrol with more efficient parasitoids, biopesticides, and judicious use of insecticides pave the way for sustainable management of M. vitrata, which can reduce the pesticide misuse. Active engagement of the private sector and policy makers can increase the adoption of integrated pest management approaches in food legumes.